Me Literature Review: Taksonomi dan Morfologi Syzygium: Literature Review: Taksonomi dan Morfologi Syzygium - Amriyah Ummi Ma'rifah; Eryka Oktaviana; Muhammad Imam Badruttamam (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
Syzygium is the largest genus in the myrtle family (Myrtaceae) with about 1200 species. Syzygium ranks 16th out of 57 genera of flowering plants, or even in the top 10. Syzygium is found in tropical or subtropical vegetation, tropical rainforests, lowlands, mountains, swamps, savannas and limestone forests. The fruit of the genus Syzygium is something that is most widely used and also cultivated, for example S. aqueum, S. cumini, S. jambos, and S. malaccense are important and commonly cultivated. The development of taxonomy in living things is marked by the popularity of the scientific naming of an organism with the binomial nomenclature system by Carrolus Linnaeus in 1758. The first time the name Syzygium was adopted with the name Suzygium. Syzygium etymologically comes from the Latin syzygia and from the Greek Sysygos which means yoke together. In Species Plantarum, five species are included which are currently accepted as Syzygium in three separate genera including Caryophyllus L., Eugenia L., and Myrtus L. Currently, there are two views of thought for the Syzygium classification scheme approach. The DNA sequence phylogeny approach and morphological evidence in its classification, support the generic concept of Syzygium which includes all, but with infrageneric classification to reflect the evolutionary relationships between clades. According to them, the molecular evidence gathered to establish a robust phylogenetic genera, the broad concept of Syzygium will temporarily eliminate the need to create more new genera to accommodate new morphological characters.